Psychotherapy Is Chaotic—(Not Only) in a Computational World - Schiepek, Günter K.; Viol, Kathrin; Aichhorn, Wolfgang; Hütt, Marc-Thorsten; Sungler, Katharina; Pincus, David; Schöller, Helmut J. (Frontiers in Psychology, 2017)
Objective: The aim of this article is to outline the role of chaotic dynamics in psychotherapy. Beside some empirical findings of chaos at different time scales, the focus is on theoretical modelling of change processes explaining and simulating this kind of dynamics. It will be illustrated how some common factors of psychotherapeutic change and psychological hypotheses on motivation, emotion regulation, and information processing of the client’s functioning can be integrated into a comprehensive nonlinear model of human change processes. Methods: The model combines 5 variables (intensity of emotions, problem intensity, motivation to change, insight and new perspectives, therapeutic success) and 4 parameters into a set of 5 coupled nonlinear difference equations. The simulations are presented by time series, the phase space embedding of the time series (attractors), and bifurcation diagrams. Results: The model creates chaotic dynamics, phase transition like phenomena, bi- or multi-stability, and sensibility of the dynamic patterns on parameter drift. These features are predicted by chaos theory and by Synergetics and correspond to empirical findings. The spectrum of these behaviors illustrates the complexity of psychotherapeutic processes. Conclusion: The model contributes to the development of an integrative conceptualization of psychotherapy. It refers to the knowlegde on common factors and other psychological topics like motivation, emotion regulation, and cognitive processing. The role of chaos theory in the virtual world of computer simulations, but also in practice is underpinned. In practice, it asks for technologies of real-time monitoring reporting on the nonlinear features of the ongoing process (e.g., its stability or instability) and for a client-centered continuous cooperative process control, and doubts the usefulness of manuals or other predefined programs.